A Study of Translation of Masnavi Molana Room by Qazi Sajjad Hussain - Akhtar, Naheed; Shakir, Sanam; Irshad, Saira (sourcecoder, 2022)
Maulana Romi is an important name (personality) in the Eastern Islamic State. In particular, “Masnavi Maulana Romi” is his masterpiece. Written in Persian, this Masnavi is a beautiful example of high values, wisdom,and philosophy and Islamic mysticism. This translated to almost all important and major languages of the world. There are many Translations in Urdu as well. One of them is the important effort of Qazi Sajjad Hussain. Who has completed this translation with separate features. In the following article, important features of Qazi Sajjad Hussain’s translation have been pointed out. So that the presence of other translations can make clear the value, importance and usefulness of this translation